Long-Term Adherence to Low-Sodium Diet in Patients With Heart Failure. (April 2017) - Chung, Misook L.; Park, Linda; Frazier, Susan K.; Lennie, Terry A.
Although following a low-sodium diet (LSD) for heart failure (HF) has been recommended for decades, little is known about factors related to long-term patient adherence. The purposes of this study were to (a) compare sodium intake and factors affecting adherence in a long-term adherent group and in a non-adherent group and (b) examine predictors of membership in the long-term adherent group. Patients with HF ( N = 74) collected 24-hr urine samples and completed the Dietary Sodium Restriction Questionnaire and the Patient Health Questionnaire-9. Long-term adherence was determined using the Stage of Dietary Behavior Change Scale. The long-term adherent group had lower sodium intake (3, 086 mg vs. 4, 135 mg, p = .01) and perceived more benefits from LSD than the non-adherent group. Only positive attitudes toward LSD predicted membership in the long-term adherence group (odds ratio [OR] = 1.18, p = .005). Interventions focused on enhancing positive perceptions of the benefits of an LSD may improve long-term dietary adherence in patients with HF.